Predictors of success for electronic health record implementation in small physician practices - Ancker, J.S.; Singh, M.P.; Thomas, R.; Edwards, A.; Snyder, A.; Kashyap, A.; Kaushal, R. (Applied Clinical Informatics, 2013)
Background: The federal government is promoting adoption of electronic health records (EHRs) through financial incentives for EHR use and implementation support provided by regional extension centers. Small practices have been slow to adopt EHRs.Objectives: Our objective was to measure time to EHR implementation and identify factors associated with successful implementation in small practices receiving financial incentives and implementation support. This study is unique in exploiting quantitative implementation time data collected prospectively as part of routine project management.Methods: This mixed-methods study includes interviews of key informants and a cohort study of 544 practices that had worked with the Primary Care Information Project (PCIP), a publicly funded organization that since 2007 has subsidized EHRs and provided implementation support similar to that supplied by the new regional extension centers. Data from a project management database were used for a cohort study to assess time to implementation and predictors of implementation success.Results: Four hundred and thirty practices (79%) implemented EHRs within the analysis period, with a median project time of 24.7 weeks (95% CI: 23.3 – 26.4). Factors associated with implementation success were: fewer providers, practice sites, and patients; fewer Medicaid and uninsured patients; having previous experience with scheduling software; enrolling in 2010 rather than earlier; and selecting an integrated EHR plus practice management product rather than two products. Interviews identified positive attitude toward EHRs, resources, and centralized leadership as additional practice-level predictors of success.Conclusions: A local initiative similar to current federal programs successfully implemented EHRs in primary care practices by offsetting software costs and providing implementation assistance. Nevertheless, implementation success was affected by practice size and other characteristics, suggesting that the federal programs can reduce barriers to EHR implementation but may not eliminate them.Citation: Ancker JS, Singh MP, Thomas R, Edwards A, Snyder A, Kashyap A, Kaushal R. Predictors of success for electronic health record implementation in small physician practices. Appl Clin Inf 2013; 4: 12–24http://dx.doi.org/10.4338/ACI-2012-09-RA-0033
Keywords: Electronic health records; ambulatory care/primary care; implementation and deployment; facilitators and barriers; quantitative methods; mixed methods